STUDI FENOMENOLOGIS PENGALAMAN SISWA PADA SEKOLAH SMPIT AL FAJAR DESA SEI MENCIRIM DALAM MENGHADAPI DIDIKAN KERAS ORANG TUA DAN IMPLIKASINYA TERHADAP PENDIDIKAN AGAMA - Adelisia Pramudita; Munawir Pasaribu (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This study aims to examine students’ experiences in facing harsh parental discipline and its implications for their attitudes toward Islamic Religious Education (PAI) learning. This research employed a qualitative method with a phenomenological approach to understand students' subjective experiences in depth. The study was conducted at SMPIT Al Fajar in Sei Mencirim Village involving one class as the research subject. The research informants consisted of several students, one Islamic Religious Education teacher, and a homeroom teacher. Data were collected through in-depth interviews and observation. The data were analyzed using descriptive qualitative analysis through data reduction, data display, and conclusion drawing. The results of the study indicate that some students experience harsh parental discipline such as being scolded with a loud voice, being compared with peers, and receiving light punishment when neglecting religious obligations or when their academic performance decreases. These experiences generate various emotional responses among students, including fear, sadness, and psychological pressure. Such conditions also influence students’ attitudes in the Islamic Religious Education learning process at school. Some students tend to show low self-confidence, become passive during learning activities, and feel afraid of making mistakes, especially in religious practice activities such as prayer, ablution, and Qur’an recitation. This study highlights that parenting patterns in the family environment have an influence on students’ learning attitudes and their interpretation of religious education at school.